Chemistry : decade by decade - Greenberg, Arthur (New York : Facts on File, 2007)
Looks at the history of chemistry throughout the twentieth-century.
Includes bibliographical references and index.
Keywords: Chemistry -- History -- 20th century; Chemistry -- Study and teaching